2008
DOI: 10.1111/j.1471-8286.2007.01992.x
|View full text |Cite
|
Sign up to set email alerts
|

TECHNICAL ADVANCES: Effects of genotyping protocols on success and errors in identifying individual river otters (Lontra canadensis) from their faeces

Abstract: In noninvasive genetic sampling, when genotyping error rates are high and recapture rates are low, misidentification of individuals can lead to overestimation of population size. Thus, estimating genotyping errors is imperative. Nonetheless, conducting multiple polymerase chain reactions (PCRs) at multiple loci is time-consuming and costly. To address the controversy regarding the minimum number of PCRs required for obtaining a consensus genotype, we compared consumer-style the performance of two genotyping pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
34
2
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 42 publications
(114 reference statements)
5
34
2
1
Order By: Relevance
“…For all the tested samples, the same consensus genotypes were reached with fewer PCRs (22% less) than the multi-tubes approach of Taberlet et al (1996). Theses results are consistent with those obtained by Hansen et al (2008) who compared both methods using otter's faeces. These authors showed that, on average, 4.5 (±0.5) positive PCRs were needed with the comparative approach compared to an average of 6.8 (±0.6) for the multi-tubes protocols (corresponding thus to a decrease of *33%).…”
Section: Sampling Strategysupporting
confidence: 91%
See 2 more Smart Citations
“…For all the tested samples, the same consensus genotypes were reached with fewer PCRs (22% less) than the multi-tubes approach of Taberlet et al (1996). Theses results are consistent with those obtained by Hansen et al (2008) who compared both methods using otter's faeces. These authors showed that, on average, 4.5 (±0.5) positive PCRs were needed with the comparative approach compared to an average of 6.8 (±0.6) for the multi-tubes protocols (corresponding thus to a decrease of *33%).…”
Section: Sampling Strategysupporting
confidence: 91%
“…Our error rates (overall 5-39% for the dropout allele) were comparable to those of other studies using faeces (Morin et al 2001;Hansen et al 2008). Some loci provided much lower error rates than others (e.g., 93HDZT164 compared to 93HDZT265), and a wider-scale analysis would be required to determine the factors responsible for these differences (Taberlet et al 1999;Hansen et al 2008). Altogether our results suggest that it should be possible to significantly reduce the cost of faecal DNA studies without reducing the quality of the genotypes.…”
Section: Sampling Strategysupporting
confidence: 88%
See 1 more Smart Citation
“…The Mh estimator is a model derived to look at individual differences in capture probability and has relatively widespread use (Chao & Huggins, 2005). The Mh model is ideal with non-invasive genetic sampling where variability in sampling frequency for identified individuals is often apparent (Mills et al, 2000;Frantz et al, 2003;Hansen et al, 2008) and has been used previously in the estimation of population size for woodland caribou populations (Hettinga, 2010).…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Thus, false genotypes may occur which are recorded as new capture events instead of recaptures. Methodological improvements have been proposed that reduce the risk of genotyping errors, such as scoring alleles based on several PCR replicates (Navidi et al 1992;Taberlet et al 1996;Goossens et al 2000;Hansen et al 2008). …”
Section: Introductionmentioning
confidence: 99%